A multi-omic survey of black cottonwood tissues highlights coordinated transcriptomic and metabolomic mechanisms for plant adaptation to phosphorus deficiency - Kangi, Emel; Brzostek, Edward R.; Bills, Robert J.; Callister, Stephen J.; Zink, Erika M.; Kim, Young-Mo; Larsen, Peter E.; Cumming, Jonathan R. (Frontiers in Plant Science, 2024)
Phosphorus (P) deficiency in plants creates a variety of metabolic perturbations that decrease photosynthesis and growth. Phosphorus deficiency is especially challenging for the production of bioenergy feedstock plantation species, such as black cottonwood (Populus spp.), where fertilization may not be practically or economically feasible. While the phenotypic effects of P deficiency are well known, the molecular mechanisms underlying whole-plant and tissue-specific responses to P deficiency, and in particular the responses of commercially valuable hardwoods, are less studied. To fill this knowledge gap, we used a multi-tissue and multi-omics approach using transcriptomic, proteomic, and metabolomic analyses of the leaves and roots of P-deficient and replete Populus trichocarpa (P. trichocarpa) seedlings. As expected, P-deficient plants had reduced dry biomass, altered chlorophyll fluorescence, and reduced tissue P concentrations. In line with these observations, growth, C metabolism, and photosynthesis pathways were downregulated in the transcriptome of the P-deficient plants. Transcriptomics data suggested the molecular mechanisms by which black cottonwood seedlings altered their carbon allocation. Additionally, we found evidence of stronger lipid remodeling in the leaves, which we hypothesize is one mechanism whereby P deficiency leads to greater declines in total root tissue P concentrations. Unexpectedly, the metabolome data showed that the roots of P-deficient plants had a greater relative abundance of phosphate ion, which may reflect extensive degradation of P-rich metabolites in plants exposed to long-term P-deficiency. With the notable exception of the KEGG pathway for Starch and Sucrose Metabolism (map00500), the responses of the transcriptome and the metabolome to P deficiency were consistent with one another. Interestingly, no significant changes in the proteome were detected in response to P deficiency. Collectively, our multi-omic and multi-tissue approach enabled the identification of important metabolic and regulatory pathways regulated across tissues at the molecular level that will be important avenues for future research.